Exon-intron organization and complete nucleotide sequence of a human major histocompatibility antigen DC beta gene. - Larhammar, D (1983)
We have determined the complete nucleotide sequence of a human class II histocompatibility antigen DC beta gene. The gene spans more than 7 kilobases and contains five exons corresponding to the different domains of the DC beta polypeptide. The exon-intron organization is thus analogous to that of class II antigen alpha-chain genes, class I antigen heavy chain genes, and the constant parts of immunoglobulin genes, emphasizing further the evolutionary relationship among these molecules. The mature polypeptide deduced from the DC beta gene shows 93% and 88% homology, respectively, to sequences derived from two DC beta cDNA clones of other haplotypes. The allelic polymorphism of DC beta chains resides predominantly in the first extracellular domain, whereas the rest of the polypeptide is virtually constant. The exons of the DC beta gene display high homology to the corresponding exons of a murine I-A beta gene. Also, the introns show significant homology. The DC beta chains lack eight amino acids in the cytoplasmic tail, as compared to DR and I-A beta chains. This is probably due to a nonfunctional splice junction of DC beta genes, causing a separate cytoplasmic exon to be nonexpressed.